Trypanosoma cruzi Coexpressing Ornithine Decarboxylase and Green Fluorescence Proteins as a Tool to Study the Role of Polyamines in Chagas Disease Pathology. (1st June 2011) - Barclay, Jeremías José; Morosi, Luciano Gastón; Vanrell, María Cristina; Trejo, Edith Corina; Romano, Patricia Silvia; Carrillo, Carolina
Abstract : Polyamines are essential for Trypanosoma cruzi, the causative agent of Chagas disease. As T. cruzi behaves as a natural auxotrophic organism, it relies on host polyamines biosynthesis. In this paper we obtained a double-transfected T. cruzi parasite that expresses the green fluorescent protein (GFP) and a heterologous ornithine decarboxylase (ODC), used itself as a novel selectable marker. These autotrophic and fluorescent parasites were characterized; the ODC presented an apparent Km for ornithine of 0.51 ± 0.16 mM and an estimated Vmax value of 476.2 nmoles/h/mg of protein. These expressing ODC parasites showed higher metacyclogenesis capacity than the auxotrophic counterpart, supporting the idea that polyamines are engaged in this process. This double-transfected T. cruzi parasite results in a powerful tool—easy to follow by its fluorescence—to study the role of polyamines in Chagas disease pathology and in related processes such as parasite survival, invasion, proliferation, metacyclogenesis, and tissue spreading.